Pengaruh Kualitas Akun Instagram @ipbprestasi Terhadap Motivasi Berprestasi Mahasiswa IPB University - Aminaturrizqi, Nida; Nugroho, David Rizar; Muhammad, Badar; Khairunisa, Anggi Widia; Manisya, Nabhila (LUGAS Jurnal Komunikasi, 2024)
Information and Communication Technology is a primary tool to supportbroader, more flexible, and inclusive communication. One application ofthis technology is through social media, such as the Instagram account@ipbprestasi, which provides content uploaded by the @ipbprestasiInstagram account, students' achievement motivation, and the account'sinfluence on the student’s learning motivation at the IPB UniversityVocational School. The issues addressed include the quality of contentuploaded by the @ipbprestasi Instagram account, students' achievementmotivation, and the extent to which the account influences IPB Universitystudents’ learning motivation. This research employs a quantitativeapproach using survey methods and questionnaires distributed to IPBUniversity students. The findings reveal that the quality of uploadedcontent significantly impacts students' achievement motivation. Contentmanagement utilizing the 4C elements of Context, Communication,Collaboration, and Connection positively enhances students' motivation.The conclusion of this study indicates a significant influence of the@ipbprestasi Instagram account on students' learning motivation,aligning with the Uses and Gratifications theory.